Pengaruh Komunikasi Intrapersonal, Komunikasi Interpersonal dan Motivasi Terhadap Kepuasan Kerja Guru Sekolah Menengah Atas Negeri Se-Kota Baru - RUWAIDA AIDA (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2021)
The indirect influence between interpersonal communication on teacher job satisfaction.This research is conducted with a quantitative approach. The type is this reseachcorrelational research. The technique of data collection is done by using questionnaireinstruments. Data analysis which is used is path analysis assisted with smart PLS 3.2.8software. Measurement models are carried out by evaluation of the measurement model(outher model) and evaluation of the structural model (inner model). The results of thisstudy indicate that: (1) There is no significant positive effect of intrapersonalcommunication of teachers on teacher work motivation (2) There is a significant positiveeffect of teacher interpersonal communication on work motivation (3) There is asignificant positive effect of teacher intrapersonal communication on teacher jobsatisfaction (4) There is no significant positive effect of teacher interpersonalcommunication on teacher job satisfaction (5) There is a significant positive effect ofteacher work motivation on teacher job satisfaction with (6) There is no significantpositive effect of teacher intrapersonal communication on teacher job satisfactionthrough teacher work motivation (7) There is a significant positive effect of teacherinterpersonal communication on teacher job satisfaction through teacher workmotivation